APPLICATION OF ISLAMIC ENTREPRENEURSHIP VALUES (CASE STUDY ON STUDENT ENTREPRENEURS) MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Adawiah, Rabiatul; Nasir, Astia; Wahyuni, Sri; Rizaldy, Andi Risfan (Jurnal Ilmiah Al-Tsarwah, 2023)
Entrepreneurship is one of the activities to fulfill the needs that are pretty much in demand by various parties. Entrepreneurial activity can be an alternative in terms of solving economic problems. Indonesia is a nation where the majority of the people are Muslims. Muslims are the largest people in the world. However, there are still many Muslims, even those in Indonesia, who are still very minimal interested in building a business or entrepreneurship. Entrepreneurship activities basically in Islam have been taught, trained, and indoctrinated so how to become a fighter, entrepreneur, or entrepreneurship by imitating the nature of the Prophet Muhammad in entrepreneurship and also with the foundation or leading aspect of entrepreneurship contained in the Islamic values of the Qur'an and Hadith. This research was conducted by collecting several concepts which were then compiled from research variables and combined into a new scientific study, using qualitative methods, trying to discover several factors that influence a person's decision to become an entrepreneur. In addition, the purpose of this study is to add a little reference to studies related to Islamic Entrepreneurship values. A country will be strong because of its many strong entrepreneurs.